Assessment of Occupational Exposure Hazards on Farmers Due to Insecticide Control of Cacao Mirids (Insecta: Hemiptera) in Southwestern Nigeria - Sosan, Mosudi Babatunde (2015)
The study investigated the risks involved in applying selected insecticides to control mirids in cacao (Theobroma cacao L.) plantations in southwestern Nigeria.